Chronic Plasma Cell Endometritis in Hysterectomy Specimens of HIV-Infected Women: A Retrospective Analysis. Issue 4 (1998) - Kerr-Layton, J. A.; Stamm, C. A.; Peterson, L. S.; Mcgregor, J. A.
Abstract : Objective: Abnormal uterine bleeding is a common and troublesome problem in human immunodeficiency virus (HIV)-infected women. We sought to evaluate endometrial pathology among HIVinfected women requiring hysterectomy to explore if endometritis may be common among these patients. Methods: We performed a retrospective analysis of uterine pathology specimens obtained from HIV-infected and control patients requiring hysterectomy in two urban hospitals between 1988 and 1997 matched for age, surgical indication, and history of gonadotropin-releasing hormone (GnRH) use. Cases were evaluated for the presence of plasma cells and assigned a grade between 0 and 3. Results: Indications included cervical dysplasia (4), carcinoma in situ (2), abnormal uterine bleeding (3), and adnexal mass (3). Some degree of abnormal uterine bleeding occurred in all cases. Plasma cell endometritis was twice as common in HIVoinfected women compared to HIV-negative specimens (11/11 versus 11/22) ( P < 0.05). Plasma cell endometritis was also of a higher grade in specimens from HIV-infected women than in controls ( P < 0.001). Conclusion: Chronic endometritis was common and of a higher grade among HIV-infected women requiring hysterectomy in our series. Diagnosis and treatment of endometritis should be considered in HIV-infected women with uterine bleeding and/or tenderness. We speculate that antiretroviral and/or antimicrobial treatment for endometritis may effectively treat endometritis and eliminate the need for surgery in some HIV-infected women. We suggest that consideration and treatment of endometritis in HIV-1 infected women being evaluated for possible hysterectomy has the potential to reduce costs and morbidity for patients and providers who may be exposed during surgical procedures.